PENERAPAN MODEL PROBLEM BASED LEARNING BERORIENTASI HOTS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 5 MATERI SIFAT-SIFAT CAHAYA - Iffah Agustin Kusumaningtyas; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
This research was conducted with the aim of improving the learning outcomes of class 5 students on the properties of light. This research uses a classroom action research model (PTK. This PTK step consists of 2 cycles, each cycle is completed in one week. The research subjects are 5th grade students at Al Mubarok Islamic Elementary School semester 1 of the 2023/2024 academic year. The instruments used in the activity are namely written tests, documentation and observation, while evaluation focuses on test-based processes and results. The research results show that the use of Problem Based Learning (PBL) is able to improve students' learning outcomes. This can be seen in the IPAS score which has increased sharply, from 60% completeness KKTP in cycle I and increased to 95% in cycle II. The cycle ends when learning completeness reaches more than 85% in cycle II.